Innovation Capabilities and Logistics Service Quality of Malaysian Third- Party Logistics (3PL) Service Providers: A Comprehensive Review of the Relevant Literature - Siti Nur ‘Atikah Zulkiffli; Maisarah Sebadak; Siti Falindah Padlee; Juhaizi Mohd Yusof (International Journal of Supply Chain Management, 2019)
The purpose of this paper is to provide the foundation for third-party logistics (3PL) firms to become niche logistics providers. The development of this paper is based on a comprehensive literature review drawn from a total of 114 academic researches. The review reveals that 3PL firms need to consider uniqueness in the development of both their capability and service performance. As the focus should be on the capability to perform services with quality, the uniqueness that is embedded will create a competitive edge in terms of unique innovation characteristics over other competitors, locally and abroad. The uniqueness will also magnify the respective 3PL firm’s service quality in terms of its greatness. The findings indicate that future research in the area is needed as this will contribute significantly to the body of knowledge, specifically the Resource Based View (RBV) theory.